2013
DOI: 10.1161/jaha.113.000284
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term miR‐669a Therapy Alleviates Chronic Dilated Cardiomyopathy in Dystrophic Mice

Abstract: BackgroundDilated cardiomyopathy (DCM) is a leading cause of chronic morbidity and mortality in muscular dystrophy (MD) patients. Current pharmacological treatments are not yet able to counteract chronic myocardial wastage, thus novel therapies are being intensely explored. MicroRNAs have been implicated as fine regulators of cardiomyopathic progression. Previously, miR‐669a downregulation has been linked to the severe DCM progression displayed by Sgcb‐null dystrophic mice. However, the impact of long‐term ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 48 publications
0
50
0
Order By: Relevance
“…More recently, another group has shown that miR-486 is a direct target of myostatin signaling, and that genetic ablation of myostatin induces myotube hypertrophy via miR-486 and PTEN/AKT signaling (100). Several groups have shown that overexpression of muscle microRNAs can ameliorate some pathological signs of muscle disease in murine models (101,102). One can envision that miR-486 overexpression via adeno-associated virus (AAV) might have beneficial effects on dystrophin-defective muscles by promoting muscle hypertrophy and promoting regeneration (103).…”
Section: Dock3 Is An Essential Regulator Of Pten/akt and Rac1 Signalimentioning
confidence: 99%
“…More recently, another group has shown that miR-486 is a direct target of myostatin signaling, and that genetic ablation of myostatin induces myotube hypertrophy via miR-486 and PTEN/AKT signaling (100). Several groups have shown that overexpression of muscle microRNAs can ameliorate some pathological signs of muscle disease in murine models (101,102). One can envision that miR-486 overexpression via adeno-associated virus (AAV) might have beneficial effects on dystrophin-defective muscles by promoting muscle hypertrophy and promoting regeneration (103).…”
Section: Dock3 Is An Essential Regulator Of Pten/akt and Rac1 Signalimentioning
confidence: 99%
“…73 Other reports indicate that AAV9-microRNA378 attenuates cardiac hypertrophy after pressure overload because of thoracic aortic constriction 74 and that AAV9-microRNA-669a alleviates chronic dilated cardiomyopathy in dystrophic mice. 75 …”
Section: In Vivo Cardiac Expression Of Small Rnas Using Aav Vectorsmentioning
confidence: 99%
“…Sarcomere organization improved with reduced ventricular atrial natriuretic peptide and improved molecular markers of dilated cardiomyopathy. Increases in fractional shortening were also observed on long-term treatment of these mice (22). Such direct implication of miRNA-targeted therapeutic benefit brings hope to this area of investigation.…”
Section: Dilated Cardiomyopathymentioning
confidence: 79%